Ultra-orphan lysosomal storage diseases: a cross-sectional quantitative analysis of the natural history of alpha-mannosidosis - Zielonka, Matthias; Garbade, Sven; Kölker, Stefan; Hoffmann, Georg F.; Ries, Markus (Journal of inherited metabolic disease, 2019)
Purpose Alpha-mannosidosis (OMIM 248500) is a rare lysosomal storage disorder caused by a deficiency of the enzyme alpha-mannosidase. Recently, enzyme replacement therapy was approved in the European Union for the treatment of alpha-mannosidosis, but evaluation regarding long-term efficacy and safety is hard to assess due to missing quantitative natural history data, in particular survival. Methods We performed a quantitative analysis of published cases (N=111) with alpha-mannosidosis. Main outcome measures were age of disease onset, diagnostic delay and survival (overall and by subgroup exploration). Residual alpha-mannosidase activity and age of onset were explored as potential predictors of survival. STROBE criteria were respected. Results Median age of onset was 12 months. Median diagnostic delay was 6 years. At the age of 41 years 72.3% of patients were alive (N=111). Residual alpha-mannosidase activity (N=34) predicted survival: Patients with a residual alpha-mannosidase activity below or equal to 4.5% of normal in fibroblasts had a median survival of 3.5 years, whereas patients with alpha-mannosidase activity above this threshold all survived during the observation period reported. Patients with age of onset above 7 years survived significantly longer than patients with age of onset below or equal to 7 years. Patient distribution was panethnic with hotspots in the USA and Germany. Synopsis We defined age of onset, diagnostic delay and survival characteristics in a global cohort of 111 patients with alpha-mannosidosis by retrospective quantitative natural history modeling. These data expand the quantitative understanding of the clinical phenotype. This article is protected by copyright. All rights reserved.
Gesehen am 30.10.2019